Mr. Blackwell with museum colleagues - Unidentified photographer (Colorado State University. Libraries, 1996)
Photograph of Linda Carlson, Mr. Blackwell, Antigone Kotsiopulos, and Robert Spencer. They are posing in front of an exhibition case of Mr. Blackwell garments.
Keywords: Fashion -- History; Fashion -- Exhibitions